2015
DOI: 10.1080/00221546.2015.11777365
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Silence: The Unionization of Postdoctoral Workers at the University of California

Abstract: This article examines the postdoctoral unionization movement at the University of Cali

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The incentives of faculty members to hire postdocs are clear. Some postdocs feel abused by these financial and work‐related realities and have formed labour unions, as in the University of California system, with 6500 postdocs in UAW Local 5810 (Camacho and Rhoads, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incentives of faculty members to hire postdocs are clear. Some postdocs feel abused by these financial and work‐related realities and have formed labour unions, as in the University of California system, with 6500 postdocs in UAW Local 5810 (Camacho and Rhoads, ).…”
Section: Introductionmentioning
confidence: 99%
“…Number of postdocs in the US by major field 1987–2014. Data source: Survey of Doctorate Recipients (National Science Foundation, ). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Introductionmentioning
confidence: 99%
“…During this time, I conducted two pilot studies to explicitly understand power dynamics within the postdoctorate. The first study provided information as to why establishing a union was necessary for the general welfare of the population (Camacho & Rhoads, 2015). The second study confirmed statistically significant differences between resident and nonresident postdocs as it pertained to labor violations, in which nonresident postdocs experienced additional labor violations.…”
Section: Transformative Mixed Methods Study Designmentioning
confidence: 99%
“…However, the postdoctorate is oftentimes experienced as a low-paying academic position that offers limited employment stability (NRC, 2000; NRC 2005a, 2005b; NSF, 2009; Stephan, 2012). For the IPD community, workplace vulnerability may be exacerbated due to their temporary worker status (Camacho, & Rhoads, 2015; Cantwell & Lee, 2010; Stephan, 2012). Issues of visa types, various degrees of rights and freedoms, institutional power dynamics, workplace advocacy, and the fragility of one’s academic reputation are inherent matters to the IPD workforce (Camacho, & Rhoads, 2015; Cantwell & Lee, 2010; Stephan, 2012).…”
Section: Objective and Background For The Studymentioning
confidence: 99%
“…At the same time, researchers have pointed out that regardless of the factors deriving the decision to merge, specific circumstances of an individual institution greatly influence the change process and the way it is perceived by its stakeholders (Mathieson, 2012;Chen et al, 2010). This justifies the predominate application of case study research in this area (Almansour and Kempner, 2015;Camacho and Rhoads, 2015).…”
Section: Introductionmentioning
confidence: 99%